2005
DOI: 10.1158/1535-7163.mct-04-0329
|View full text |Cite
|
Sign up to set email alerts
|

Tumor penetration of gefitinib (Iressa), an epidermal growth factor receptor tyrosine kinase inhibitor

Abstract: The relative distribution of gefitinib-related material in nude mice bearing s.c. human tumor xenografts and in an orthotopic rat lung tumor model was investigated following oral administration (50 mg/kg) of [14 C]-gefitinib. Selected tissue samples were monitored for radioactivity by liquid scintillation counting, whereas plasma and tumor extracts were assayed for gefitinib and its major metabolites (M523595 and M537194) by high-performance liquid chromatography with tandem mass spectrometric detection. Tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
86
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 29 publications
12
86
1
Order By: Relevance
“…Patients were moved onto non-EIAEDs before study entry, to exclude reduced drug exposure through induction of CYP3A4. Intratumoral gefitinib concentrations reached 22-fold higher concentrations in the resected tumor tissue than in coincident plasma samples, consistent with previous reports from lung and breast cancer (28,29 Figure 5. Modulation of the EGFR signaling pathway.…”
Section: Discussionsupporting
confidence: 91%
“…Patients were moved onto non-EIAEDs before study entry, to exclude reduced drug exposure through induction of CYP3A4. Intratumoral gefitinib concentrations reached 22-fold higher concentrations in the resected tumor tissue than in coincident plasma samples, consistent with previous reports from lung and breast cancer (28,29 Figure 5. Modulation of the EGFR signaling pathway.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the technical problems associated with phosphoprotein immunostaining and the fact that these two studies were not designed to specifically determine target inactivation in HER2-overexpressing tumors at maximal drug dosage, they do appear to suggest that the drugs do reach their tumor targets and at least partially inactivate them. Tumor biodistribution does not seem to be a limiting step since, at least with regards to gefitinib, tumor and tissue concentrations have been measured and are much higher than serum concentrations and well above concentrations that fully suppress EGFR and HER2 signaling in cell-culture models (McKillop et al, 2005). (Sergina et al, 2007).…”
Section: Evidence That Her Tkis Inhibit Her2 Function In Patientsmentioning
confidence: 99%
“…These studies appear to show that TKIs do reduce EGFR and HER2 autophosphorylation and downstream MAPK signaling, however a reduction in Akt signaling has not been seen 80,81 . Tissue biodistribution does not seem to be a limitation and at least in the case of gefitinib, drug levels in tumor tissue appear to be well within the expected therapeutic range 82 . Our laboratory recently gained considerable insight into breast cancer resistance when we found that HER3 escapes inhibition by TKI therapy in HER2-overexpressing breast cancers 83 .…”
Section: Mechanisms Of Resistance To Her Tkismentioning
confidence: 97%